Role of time preferences in explaining the burden of malnutrition: Evidence from urban India - Archana Dang (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
This study uses a simple theory model to examine how time preferences influence food choices made by individuals, which in turn have implications for their future health. The theory results demonstrate that individuals with higher bias for the present or lower patience will have poorer health outcomes: that is, they will either be underweight (low BMI) or overweight (high BMI). The pathway from time preferences to BMI is through food. To empirically validate these predictions, we use both the nationallyrepresentative India Human Development Survey (IHDS) to estimate a reduced form equation relating savings (a proxy for time preferences) to BMI; and a primary survey of 885 adults conducted in West Delhi. Using quantile regression and SEM estimation, we provide empirical validation for the theory results; namely that time preferences have significant effect on food choices which in turn has a significant impact on BMI. Thus, such psychometric measures are useful in identifying early on those at potential risk of being overweight or obese later as adults.
Keywords: I12; I15; I18; D91; C93; 330; BMI; overweight or obese; underweight; time preferences; time inconsistency; time consistency; present bias; risk and time discounting